Novel Agents and Future Prospects in the Treatment of Pancreatic Adenocarcinoma - Sarris, Evangelos G; Syrigos, Kostas N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic adenocarcinoma is one of the most aggressive malignancies and the fourth leading cause of cancer-related mortality in the United States. The majority of patients are diagnosed at advanced stage with inoperable locally advanced tumors or metastatic disease, and palliative chemotherapy remains the best therapeutic option for these patients. Despite intensive clinical and pre-clinical research over the last few years, the combination of the anti-metabolite drug gemcitabine with the targeted agent erlotinib, is considered standard of care in the treatment of these patients, with only minimal or modest efficacy. Therefore, novel therapeutic approaches are currently under clinical investigation in an attempt to produce more definite results for this fatal disease. In this paper we summarize five most interesting research abstracts as presented at the 2013 American Society of Clinical Oncology (ASCO) Annual Meeting. In two studies, nimotuzumab, a monoclonal antibody against epidermal growth factor receptor (EGFR) (Abstract #4009) and bavituximab, a monoclonal antibody against phosphatidylserine (Abstract #4054) are tested in combination with gemcitabine in patients with advanced pancreatic cancer. Abstract #4012 is a study of gemcitabine with vismodegib, a novel hedgehog pathway inhibitor, whereas in Abstract #4035, toxicity and efficacy results of sunitinib in combination with gemcitabine in patients with pancreatic adenocarcinoma are presented. Lastly, safety results of pimasertib, a novel mitogen-activated protein kinase kinase (MEK) inhibitor, combined with the standard gemcitabine are presented in Abstract #4041. Image: Sophia Engastromenou Schliemann: founder of the "Sotiria" ("Salvation") Hospital (Athens, Greece) in 1902.